THE UNITED STATES AND CINO-PAK STRATEGIC IMPERATIVE IN AFGANISTAN: Pentingnya Strategi Negara-Negara Perserikatan dan Cina-Pakistan di Afganistan - nuruddin nuruddin; Ahmad Efendi (UIN Mataram, 2023)
This study aims to explain the importance of the strategy that must be taken by countries that are directly involved in war, such as the United States and Afghanistan. On the other hand, this strategy should also become an option for dominant countries in the region, such as China and China-Pakistan. This study tries to use Joseph Nye's theories/concepts, namely hard power, soft power and smart power. Soft power and smart power have been proposed for their application to try to end the violence in Afghanistan when the theory/concept of hard power has not succeeded in making Afghanistan peaceful. The methodology used in this study is explanatory-literary research, which tries to decipher the problem of the theme above based on the literature by explaining the relationship between phenomena recorded through various books, journals and reviews and what is widespread in online media. The result is then the need for a new strategy to try to reconcile the conflict/war in Afghanistan to be taken by the countries involved as well as countries that have a dominant role in Afghanistan such as China and Pakistan as the closest (neighboring) countries. The theoretical implication is that Joseph Nye's theory of soft power and smart power provides a promising solution in the future, even though this theory dates back to 2004. While the practical implications are expected that countries involved in the war and countries that have a dominant role can take this theory as their policy choice to end the conflict in Afghanistan